Bioinspired design of Na-ion conduction channels in covalent organic frameworks for quasi-solid-state sodium batteries - Yingchun Yan; Zheng Liu; Ting Wan; Weining Li; Zhipeng Qiu; Chunlei Chi; Chao Huangfu; Guanwen Wang; Bin Qi; Youguo Yan; Tong Wei; Zhuangjun Fan (Nature Communications, 2023)
Abstract Solid polymer electrolytes are considered among the most promising candidates for developing practical solid-state sodium batteries. However, moderate ionic conductivity and narrow electrochemical windows hinder their further application. Herein, inspired by the Na+/K+ conduction in biological membranes, we report a (–COO–)-modified covalent organic framework (COF) as a Na-ion quasi-solid-state electrolyte with sub-nanometre-sized Na+ transport zones (6.7–11.6 Å) created by adjacent –COO– groups and COF inwalls. The quasi-solid-state electrolyte enables selective Na+ transport along specific areas that are electronegative with sub-nanometre dimensions, resulting in a Na+ conductivity of 1.30×10–4 S cm–1 and oxidative stability of up to 5.32 V (versus Na+/Na) at 25 ± 1 °C. Testing the quasi-solid-state electrolyte in Na||Na3V2(PO4)3 coin cell configuration demonstrates fast reaction dynamics, low polarization voltages, and a stable cycling performance over 1000 cycles at 60 mA g–1 and 25 ± 1 °C with a 0.0048% capacity decay per cycle and a final discharge capacity of 83.5 mAh g−1.